Identification of a Novel 15q21.1 Microdeletion in a Family with Marfan Syndrome - Rencong Yang; Wu Zhang; Hua Lu; Jinlong Liu; Yu Xia; Shengjie Liao; Xiaohui Li; Xiaoshen Zhang; Xiaoping Fan; Chaojie Wang (Genetics Research)
Background. Marfan syndrome (MFS) is a connective tissue disease involving multiple systems, with thoracic aortic aneurysm (TAA) as the most common life-threatening manifestation. Method. A pedigree with TAA was investigated, and peripheral venous blood was extracted from six family members. After whole exome sequencing (WES) and chromosomal microarray analysis (CMA) in these individuals, bioinformatics and inheritance analyses were performed. Result. WES revealed a novel, small, 0.76 Mb microdeletion in 15q21.1, which cosegregated with the disease phenotype in the family and led to the haploinsufficiency of the fibrillin 1 (FBN1) gene, which is associated with MFS. This small copy number variant (CNV) was confirmed by CMA. Conclusion. Our study expands the phenotypic spectrum of the pathogenic CNV associated with MFS, thereby facilitating clinical genetic diagnosis and future genetic counseling for this family.